The Effect of Group-Individual Collaborative Testing on Primary Students’ Achievement in Reading Test - Yuliyanto Chandra (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
Collaborative testing—a two-stage testing modality in which students do tests as a group and individually—has been extensively researched and found to improve learning. However, most collaborative testing research has focused on non-English language learning. Therefore, this study examines the effects of group-individual collaborative testing (GICT) on English reading test achievement and student views of GICT. This sequential explanatory mixed-methods study gathered quantitative data from both treatment and control groups, primarily comprising students' correct answers, followed by qualitative insights derived from students' reflections on their learning experiences. Quantitative data demonstrates that GICT had a significant effect on students' reading achievement tests. While the qualitative data reveals that students considered GICT was a good reading testing modality, with some notes on the scoring method. Practice and research implications include 1) using GICT to test other language skills, 2) diversifying group composition, 3) giving more weight to the individual part score because students will retrieve more information during this stage, and 4) instilling collaborative learning values before testing.